Discovery of genes with highly restricted expression patterns in the Drosophila wing disc using DNA oligonucleotide microarrays. - Butler, M.J.; Jacobsen, T.L.; Cain, D.M.; Jarman, M.G.; Hubank, M.; Whittle, J.R.; Phillips, R.; Simcox, A. (Development, 2003)
The Drosophila wing disc is divided along the proximal-distal axis into regions giving rise to the body wall (proximal), wing hinge (central) and wing blade (distal). We applied DNA microarray analysis to discover genes with potential roles in the development of these regions. We identified a set of 94 transcripts enriched (two fold or greater) in the body wall and 56 transcripts enriched in the wing/hinge region. Transcripts that are known to have highly restricted expression patterns, such as pannier, twist and Bar-H1 (body wall) and knot, nubbin and Distal-less (wing/hinge), showed strong differential expression on the arrays. In situ hybridization for 50 previously uncharacterized genes similarly revealed that transcript enrichment identified by the array analysis was consistent with the observed spatial expression. There was a broad spectrum of patterns, in some cases suggesting that the genes could be targets of known signaling pathways. We show that three of these genes respond to wingless signaling. We also discovered genes likely to play specific roles in tracheal and myoblast cell types, as these cells are part of the body wall fragment. In summary, the identification of genes with restricted expression patterns using whole genome profiling suggests that many genes with potential roles in wing disc development remain to be characterized.